Perineal ultrasound in infants with anteriorly displaced anus: A new decision-making tool for the surgeon?. Issue 142 (September 2021) - Bruzeau, Anne-Hélène; Moriau, Didier; Bahans, Claire; Mounayer, Charbel; Spampinato, Grazia; Guigonis, Vincent; Ballouhey, Quentin; Fourcade, Laurent
Abstract: Background: Anteriorly displaced anus (ADA) is defined as anterior displacement of the anus toward the perineum. Early radiologic characterization is a crucial step in guiding the first-line management. Objective: The objective of this study was to assess the urethra-to-anus distance (UAD) on perineal ultrasound in female infants under the age of 3 months with anteriorly displaced anus and to retrospectively determine a cut-off to guide the indications for surgery. Materials and methods: Perineal ultrasound was performed prospectively in female infants under the age of 3 months with determination of the UAD, during screening for congenital hip dislocation. Determinations of the UAD on perineal ultrasound and pelvic MRI were performed for anteriorly displaced anus in girls between 2011 and 2018. Results: 230 patients were included, of whom 173 were in the control group, with 52 examinations performed for anteriorly displaced anus and 5 examinations performed for vestibular anus. The mean UAD for infants under the age of 3 months was: 22.9 mm (±1.7) in healthy infants, 21.4 mm (±2.4) in infants with non-operated ADA, 17.5 mm (±1.8) in infants with operated ADA, and 10.8 mm (±1.3) in infants with anorectal malformation (ARM). A statistically significant difference was observed between the control group and the ARM group (p = 0.0001) and between the control group and the operated ADA group (p = 0.0001). The mean UAD for infants over the age of 3 months was: 25.5 mm (±4.1) in infants with non-operated ADA and 26 mm (±3) in infants with operated ADA. Conclusion: A urethra-to-anus distance of less than 17 mm appears to be a cut-off for anteriorly displaced anus in anorectal malformations.